Partial Replacement of Fish Oil in Tra Catfish (Pangasianodon hypophthalmus) Diet with Different Levels of LYSOFORTE™ Dry - Bindhu, Lakshmibai vasanthakumari; Sugumar, c; D. Esperida, Maria Glenda (Indonesian Aquaculture Society (MAI), 2016)
Phospholipids are known to play a significant role in lipid transport in crustaceans. LYSOFORTE™ is a bio-emulsifier enriched with lysophospholipids used in animal feeds to improve the digestion and absorption of fat. Objective of the current study was to evaluate the growth promoting effect and fish oil sparing effect of LYSOFORTE™ Dry in Tra Catfish (Pangasianodon hypophthalmus) diets. This study comprised four treatment groups: positive control diet (T1) with 1% fish oil, negative control diet (with 1% less fish oil) (T2), negative control diet + LYSOFORTE™ Dry (0.05%) (T3) and negative control diet + LYSOFORTE™ Dry (0.10%) (T4). Each treatment group comprised 3 replicates with 50 juveniles/replicate. Negative control treatments with LYSOFORTE at 0.05% and 0.10% improved the average body weight gain by 16.08g and 25.74g (p>0.05) with a corresponding FCR improvement of 1 point and 11 points respectively. Specific growth rate improved by 0.18%/day (0.05% LYSOFORTE™ Dry) and 0.28%/day (0.1% LYSOFORTE™ Dry). Survival percentage also improved in the negative control diets supplemented with LYSOFORTE™ Dry by 6.67%. Protein efficiency ratio increased by 0.22 (T3) and 0.11 (T4) whereas protein retention improved by 4.89% (T3) and 3.63% (T4) with respect to the negative control diet (T2). Lipid retention increased with the use of LYSOFORTE™ Dry: 27% for T3 and 37% for T4 (P<0.05). Moreover, fish fed with negative control diet with 0.10% of LYSOFORTE™ Dry showed on par performance with those fed on the positive control diet. The results suggested the potential of formulating cat fish diets with less fish oil using LYSOFORTE™ Dry